Reflection of Tawhid in 3D Miniature Art: Analysis of Surah Ibrahim 35 through Classical and Modern Tafsir - Rusdeana, Rusdeana (el Harakah: Jurnal Budaya Islam, 2025)
The relationship between Tawhid and visual art remains one of the most profound and complex dimensions of Islamic civilization. Throughout history, Muslim artists have sought to reconcile the theological principle of divine unity with the human impulse for creativity and representation. Meanwhile, research on digital and 3D visualization in Islamic education primarily addresses technological or pedagogical aspects, often without theological grounding. Very few studies attempt to connect Qur’anic exegesis (tafsir) with modern visual technologies such as 3D miniature art. This study examines the reflection of Tawhid values in 3D miniature art through a comparative analysis of Surah Ibrahim 35 based on the interpretations of Al-Qurthubi and Wahbah az-Zuhaili. By integrating classical and contemporary tafsir with the cultural phenomenon of incomplete sculptures in the Middle East, this research explores how Islamic theological principles shape artistic ethics and modern visual expressions. Using a qualitative library-based method supported by thematic and hermeneutical analysis, the study finds that Al-Qurthubi emphasizes strict preventive measures against complete visual representation to safeguard the purity of monotheism, while Wahbah az-Zuhaili adopts a contextual approach that accommodates technological development as long as it serves educational and spiritual objectives. The findings reveal that the principle of Tawhid remains a crucial ethical framework for modern Islamic art, guiding the development of 3D miniature art in a manner that avoids idolatrous tendencies while enabling creativity, cultural preservation, and religious education. The implications of this study emphasize the integration of Tawhid values into Islamic art and modern technology. It can be done by encouraging Qur’an-based creativity, promoting 3D miniature technology in Islamic education, fostering collaboration between scholars and artists, and supporting Tawhid-oriented art initiatives to enhance spiritual awareness, da‘wah, and Islamic cultural identity. Hubungan antara Tawhid dan seni visual tetap menjadi salah satu dimensi paling mendalam dan kompleks dalam peradaban Islam. Sepanjang sejarah, para seniman Muslim telah berupaya mendamaikan prinsip teologis tentang keesaan Ilahi dengan dorongan manusia untuk berkreasi dan berepresentasi. Sementara itu, penelitian mengenai visualisasi digital dan 3D dalam pendidikan Islam umumnya berfokus pada aspek teknologi atau pedagogis, sering kali tanpa landasan teologis yang kuat. Hanya sedikit studi yang berusaha menghubungkan penafsiran Al-Qur’an (tafsir) dengan teknologi visual modern seperti seni miniatur 3D. Penelitian ini mengkaji refleksi nilai-nilai Tawhid dalam seni miniatur 3D melalui analisis komparatif terhadap Surah Ibrahim ayat 35 berdasarkan penafsiran Al-Qurthubi dan Wahbah az-Zuhaili. Dengan mengintegrasikan tafsir klasik dan kontemporer serta fenomena budaya patung tidak lengkap di Timur Tengah, penelitian ini mengeksplorasi bagaimana prinsip teologis Islam membentuk etika artistik dan ekspresi visual modern. Melalui metode kualitatif berbasis kepustakaan yang didukung analisis tematik dan hermeneutik, penelitian ini menemukan bahwa Al-Qurthubi menekankan langkah-langkah preventif yang ketat terhadap representasi visual yang sempurna demi menjaga kemurnian tauhid, sementara Wahbah az-Zuhaili mengadopsi pendekatan kontekstual yang mengakomodasi perkembangan teknologi selama bertujuan edukatif dan spiritual. Hasil penelitian menunjukkan bahwa prinsip Tawhid tetap menjadi kerangka etis yang sangat penting bagi seni Islam modern, yang berfungsi membimbing pengembangan seni miniatur 3D agar terhindar dari kecenderungan penyembahan berhala, sekaligus mendorong kreativitas, pelestarian budaya, dan pendidikan keagamaan. Implikasi dari penelitian ini menekankan pentingnya integrasi nilai-nilai Tawhid dalam seni Islam dan teknologi modern, yang dapat dilakukan dengan mendorong kreativitas berbasis Al-Qur’an, memanfaatkan teknologi miniatur 3D dalam pendidikan Islam, memperkuat kolaborasi antara ulama dan seniman, serta mendukung inisiatif seni berlandaskan Tawhid untuk meningkatkan kesadaran spiritual, dakwah, dan identitas budaya Islam..